2009
DOI: 10.1117/12.814435
|View full text |Cite
|
Sign up to set email alerts
|

Gridded design rule scaling: taking the CPU toward the 16nm node

Abstract: The Intel 45nm Penryn™ CPU was a landmark design, not only for its implementation of high-K metal gate materials 1 , but also for the adoption of a nearly gridded design rule (GDR) layout architecture for the poly silicon gate layer 2 . One key advantage of using gridded design rules is reduction of design rules and ease of 1-dimensional scaling compared to complex random 2-dimensional layouts. In this paper, we demonstrate the scaling capability of GDR to 16nm and 22nm logic nodes. Copying the design of publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…al. [7] project that the metal 1(M1) pitch for the 16nm technology node is 40nm. This is equal to 5λ where λ=8nm for 16nm technology node.…”
Section: Cmos Design Rules Applied To the Fabricmentioning
confidence: 99%
See 2 more Smart Citations
“…al. [7] project that the metal 1(M1) pitch for the 16nm technology node is 40nm. This is equal to 5λ where λ=8nm for 16nm technology node.…”
Section: Cmos Design Rules Applied To the Fabricmentioning
confidence: 99%
“…The interconnects were modeled using the Predictive Technology Model (PTM) [2] [40] models. The dimensions and parameters for scaled CMOS interconnect were chosen as projected by ITRS [1] and [7]. With the help of …”
Section: Behavioral Model Creation For Circuit Simulation In Hspicementioning
confidence: 99%
See 1 more Smart Citation
“…PTM interconnect RC models based on scaled interconnect dimensions were used in conjunction with the PTM transistor models for power and performance evaluation of GNTRAM using HSPICE. For physical layout design and area evaluation of GNTRAM, 1-D gridded design rules [Bencher et al 2009] were used as shown in Table II. For benchmarking against CMOS, 16nm Gridded 8T SRAM cell [Greenway et al 2008] was used, since this SRAM design utilizes the same grid-based design used in GNTRAM. Regular 6T CMOS SRAM scaled to 16nm technology node was also used for benchmarking.…”
Section: Methodology and Benchmarkingmentioning
confidence: 99%
“…Aerial images were calculated in order to evaluate the impact of the mask topography without the effect of photoresist. 1D mask layouts were used in order to conform to the gridded design layouts currently used by industry [12]. The mask was an unbiased dual trench (π/3π) alternating phase shift mask (AltPSM) of chromium oxide on quartz, with etch depths of 85.7/257.1 nm, duty ratio of 1:1, and a pitch of 90, 100, or 110 nm.…”
Section: Optimization Approachmentioning
confidence: 99%